DİJİTAL BAĞIMLILIK İLE TOPLUMSAL DEĞERLERİN ETKİLEŞİMİ: ÖZNEL DİNDARLIK VE SOSYODEMOGRAFİK DEĞİŞKENLERE DAYALI SOSYOLOJİK BİR ARAŞTIRMA. - AHMEDİ, Ekber Şah; KILIÇ AHMEDİ, Büşra; ÇATMA, Latife (Dinbilimleri Journal, 2026)
The digitalization process gained a concrete form with the advent of the Internet and led to a revolutionary transformation in the social structure. While digitalization has enriched human life, it has also led to the emergence of issues such as digital addiction. Digital addiction, which erodes human psychosocial functionality, describes the pathological relationship formed with technology. An overview of relevant literature reveals that addiction is mostly discussed in the fields of medicine, psychiatry, and psychology, whereas the sociological dimension of the issue has been relatively less studied. This study approaches digital addiction from a sociological perspective and seeks to contribute to the literature by incorporating social values into the analytical framework. Specifically, it aims to examine the relationship between digital addiction and social values. The study sample consists of 443 people residing in Bursa. The results revealed a statistically significant negative relationship between the two variables (r = -0.320, p < 0.01). Accordingly, higher levels of social values are associated with lower levels of digital addiction; in contrast, as digital addiction increases, commitment to social values tends to decline. It can be argued that the presence of a self-regulatory system grounded in social values is associated with lower levels of digital addiction; conversely, as digital addiction increases, adherence to social values tends to decline. As the findings demonstrate, social values play a crucial role in maintaining a social control system, mitigating addiction and similar deviant behaviors, and supporting the construction of a strong external social control system. Internalized social values, significantly contribute to the development of a self-control system and protect individuals from deviant behaviors, such as addiction. The process of digitalization has led to an extraordinary transformation in communication technology. However, the emergence of problems related to digital technological objects during this process has caused the nonmaterial dimension of culture to lag behind material cultural developments, leading to cultural lags such as digital addiction. Addiction, a multifactorial problem that erodes human individual and social functioning, requires a multidisciplinary approach with biopsychosocial dimensions. Therefore, studying the different dimensions of addiction using quantitative and qualitative methods and techniques in various disciplines, such as sociology and anthropology, medicine, psychiatry, and psychology, will make a significant contribution to the relevant literature. In short, it is crucial that digital platforms should be publicly monitored without eroding individual freedoms, and individuals should be protected from unethical personalized ads, post-truth, and infobesity flows to prevent digital addiction and brain rot. Taken together, the empirical findings underscore the critical importance of facilitating the adaptation of social capital, social and religious values, and cultural structures to ongoing innovation, while ensuring their effective intergenerational transmission. In this context, strengthening and institutionalizing digital literacy within the formal education system emerges as a strategic priority.